Entwicklung eines Kooperationsmodells für die Transportlogistik im Baustoff-Fachhandel - Denzer, Michael (Karlsruher Reihe Technologie und Management im Baubetrieb, 2019)
Based on the consolidation of the consignment volume of cooperating building materials traders, the logistics network will be improved and the transport efficiency of the cooperation partners will be increased. In addition to the development, the cooperation model will be evaluated by simulations on the basis of real data and the impact of the cooperation model for the total drive distance of the cooperation partners will be examined.